1992
DOI: 10.1203/00006450-199205000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Augmentation in Moderate to Life-Threatening Gaucher Disease

Abstract: ABSTRACT. Gaucher disease type 1 (GD type 1) is the most prevalent lysosomal storage disease and has its highest frequency in the Ashkenazi Jewish population. Deficiency of the enzyme, acid 8-glucosidase, results in the deposition of glucocerebroside primarily in macrophages. The accumulation of such "Gaucher cells" leads to visceromegaly, hepatic and bone marrow dysfunction, hypersplenism, and bony disease. Eleven GD type 1 patients, ages 4-52 y, with moderate to life-threatening manifestations, received 6-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 21 publications
1
35
0
1
Order By: Relevance
“…Twelve data sets (in 11 included studies 61,[82][83][84]87,93,95,96,99,107,116 ) reported change in spleen volume during ERT in terms of degree of enlargement or provided sufficient data for the appropriate calculation to be made. The results are summarised in the scatterplot shown in Figure 4.…”
Section: Spleenmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve data sets (in 11 included studies 61,[82][83][84]87,93,95,96,99,107,116 ) reported change in spleen volume during ERT in terms of degree of enlargement or provided sufficient data for the appropriate calculation to be made. The results are summarised in the scatterplot shown in Figure 4.…”
Section: Spleenmentioning
confidence: 99%
“…Often dose regimens were described as "individualised". 75,92,95 Adoption of an initial dose programme for a given patient was generally based on clinical judgement relating to disease severity and prognosis, whereas changes in regimen were usually dependent on clinical judgement regarding the speed and extent of response to therapy and the remaining scope for further improvement. The criteria exercised in these clinical judgements were rarely reported other than in descriptive terms (e.g.…”
Section: Mistry and Colleaguesmentioning
confidence: 99%
“…Although therapeutically effective to some extent (regression of organomegaly, increase in the haemoglobin concentration), 8,9 enzyme replacement is expensive, gives only limited improvement in neuronopathic disease due to the inaccessibility of the CNS 15,16 and the enzyme is not targeted to marrow macrophages. 2 Little activity was found in bone marrow cells, even immediately after marrow infusion.…”
Section: Introductionmentioning
confidence: 99%
“…According to Weinreb's analysis of 910 patients in the ICGG Gaucher Registry, 116 pre-ERT platelet numbers of ERT-treated patients averaged 140.8 × 10 3 mm -3 , with splenectomised patients (n = 267) having strikingly higher numbers (mean 28,55,61,75,82,84,87,92,95,96,99,100,111,116,120,121 ) reported change in platelet numbers during ERT. The results are summarised in Figure 7.…”
Section: Effect Of Ert On Platelet Levelsmentioning
confidence: 99%